DEVELOPMENT MODEL FOR REMOVAL TOTAL IRON IN â€œGAMBUT WATERâ€ FOR DRINKING WATER - Sutrisno -; Elizabeth Tjahjadarmawan; Fifi - (Universitas Andalas, 2008)
Â ABSTRACTÂ ThisÂ researchÂ isÂ focusedÂ onÂ characterizationÂ ofÂ activatedÂ carbonÂ fromÂ solidÂ wasteÂ CPOÂ industriesÂ andÂ applyingÂ forÂ treatmentsÂ ofÂ gambutÂ waterÂ forÂ ironÂ removalÂ inÂ aqueousÂ media.Â KeyÂ parametersÂ inÂ theÂ presentÂ studyÂ includeÂ TSS,Â DO,Â pHÂ andÂ totalÂ phenolÂ isÂ alsoÂ determinated.Â MethodsÂ ofÂ samplingÂ andÂ analyticalÂ techniquesÂ forÂ measuringÂ keyÂ parametersÂ areÂ byÂ usingÂ extendedÂ method.Â TheÂ smallÂ modelÂ hasÂ beenÂ developedÂ byÂ combiningÂ ofÂ theÂ compostingÂ andÂ adsorptionÂ technology.Â Â TheÂ coagulantÂ materialÂ suchÂ asÂ filterÂ alum,Â sodaÂ caustic,Â andÂ calciumÂ hypochloriteÂ inÂ anyÂ ratiosÂ areÂ variedÂ andÂ theÂ optimumÂ conditionÂ isÂ achieved.Â TheÂ activatedÂ carbonÂ isÂ usedÂ asÂ adsorbentÂ byÂ usingÂ columnÂ model.Â TheÂ overallÂ resultsÂ showÂ thatÂ afterÂ coagulationÂ andÂ adsorptionÂ processesÂ theÂ totalÂ iron,Â TSS,Â DOÂ andÂ pHÂ areÂ underÂ thresholdÂ levelsÂ (IndonesianÂ Regulation)Â andÂ suitableÂ forÂ drinkingÂ waterÂ meanwhileÂ otherÂ parametersÂ areÂ stillÂ uncoveredÂ inÂ thisÂ investigation.Â Tentatively,Â itÂ canÂ beÂ concludedÂ thatÂ theÂ proposedÂ gambitÂ waterÂ designÂ hasÂ achievedÂ theÂ optimumÂ condition.Â AÂ furtherÂ studyÂ onÂ theÂ improvementÂ ofÂ theÂ treatmentÂ designÂ andÂ serviceÂ timeÂ forÂ adsorptionÂ processÂ isÂ stillÂ inÂ progress.Â KeywordsÂ :Â totalÂ iron,Â gambutÂ water,Â activatedÂ carbon,Â combiningÂ model.